Assessing the Level and Diagnostic Accuracy of Osteopontin and Oral Health Status in Periodontitis Patients with/without Type-2 Diabetes Mellitus - Al-Qarakhli, Ahmed Makki A.; Al-Taweel, Firas B.; Abdul Ameer, Lubaba A.; Saliem, Saif S.; Abdulkareem, Ali A. (Brazilian Dental Science, 2022)
Objective: Periodontitis is a multifactorial inflammatory disease usually terminated with tooth loss when untreated. Type-2 diabetes mellitus (T2DM) have shown to exacerbate periodontitis. Osteopontin, is thought to play a role to induce periodontitis-associated bone resorption. Aim was to investigate the osteopontin level in gingival crevicular fluid of patients affected by periodontitis with or without T2DM, and to explore the potential of osteopontin to differentiate between periodontal health and disease. Patients and Methods: A total number of 36 subjects seeking periodontal treatment were recruited in this pilot study. Plaque index, gingival index and probing pocket depth were examined, and the osteopontin level was measured in the GCF and analysed using Enzyme-linked immunosorbent assay. Results: Plaque index and gingival index were significantly higher in T2DM with periodontitis compared to periodontitis and control groups. Both periodontitis groups showed significant increase in the osteopontin levels (p